Adding Up Peer Beliefs: Experimental and Field Evidence on the Effect of Peer Influence on Math Performance - Wu, Sherry Jueyu; Cai, Xiqian (Psychological Science, 2023)
We studied how gendered beliefs about intellectual abilities transmit through peers and differentially impact girls’ academic performance relative to boys’. Study 1 ( N = 8,029; 208 classrooms) exploited randomly assigned variation in the proportion of a child’s middle school classmates who believe that boys are innately better than girls at learning math. An increase in exposure to peers who report this belief generated losses for girls and gains for boys in math performance. This peer exposure also increased children’s likelihood of believing the gender–math stereotype, increased the perceived difficulty of math, and reduced aspirations among girls. Study 2 ( N = 547) provided proof of concept that activating a gender–math performance gap among college students reduces women’s math performance but not verbal performance. Men’s task performance was not affected. Our findings highlight how the prevalence of stereotypical beliefs in one’s ambient and peer environment, even when readily contradictable, can shape children’s beliefs and academic ability.